Intrinsic nano-diffusion-couple for studying high temperature diffusion in multi-component superalloys - Eggeler, Yolita; Kubacka, Dorota; Pichler, Peter; Wu, Mingjian; Spiecker, Erdmann (Scripta Materialia, 2021)
We present a new approach for the quantitative study of high-temperature diffusion in compositionally complex superalloys on the nano-scale. As key element, the approach utilizes the γ/γ'-microstructure itself as intrinsic nano-diffusion-couple (NDC). By establishing equilibrium at one temperature followed by annealing at a different temperature, well-defined transient states are generated which are studied using STEM-EDXS. We demonstrate this approach for a multi-component superalloy of CMSX-4 type. The temporal evolution of element concentrations is consistently revealed for γ- and γ'-forming elements and is compared to diffusion simulations based on DICTRA. Excellent agreement is obtained for Ni, Co, and Cr whereas diffusion of Al and, in particular, Re lacks behind in experiment. Finally, it is demonstrated that transient states can also be captured by in situ TEM using chip-based heating devices. The NDC approach offers great opportunities for diffusion studies in compositionally complex superalloys and might be extended to other two-phase multi-component systems.
CRIS-Team Scopus Importer:2020-10-30
Keywords: Compositionally complex superalloys; DICTRA simulation; In situ TEM; Multi-component diffusion; Solute segregation